2014
DOI: 10.1016/j.jesp.2014.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Formation, representation, and activation of contextualized attitudes

Abstract: The pervasiveness of context effects on evaluative responses has led to conflicting views as to whether evaluations reflect stable attitudinal representations that are directly retrieved from memory or online constructions on the basis of momentarily accessible attributes. The current research expands on this debate by investigating the formation, representation, and activation of contextualized attitudes, with a particular focus on the role of incidental visual cues of the environmental context. Five experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 65 publications
2
36
2
Order By: Relevance
“…Although many of these studies replicated our initial findings (e.g., Gawronski, Ye, Rydell, & De Houwer, 2014), some of them failed to reproduce the basic effects that served as the foundation for our theory (cf. .…”
supporting
confidence: 50%
“…Although many of these studies replicated our initial findings (e.g., Gawronski, Ye, Rydell, & De Houwer, 2014), some of them failed to reproduce the basic effects that served as the foundation for our theory (cf. .…”
supporting
confidence: 50%
“…Context plays a crucial role when constructing the meaning of concepts (e.g., Elliot & Maier, 2012;Gawronski et al, 2014;Mesquita et al, 2010;Schwarz, 2007). Researchers have emphasized the importance of developing mid- Art.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in cognitive psychology, social cognition, and linguistics convincingly show that taskspecific contexts play a crucial role when constructing meaning and when engaging in conceptual thought (e.g., Barrett, Wilson-Mendenhall, & Barsalou, 2014;Elliot & Maier, 2012;Gawronski, Ye, Rydell, & De Houwer, 2014;Mitchell, Nosek, & Banaji, 2003;Paradis & Willners, 2011;Rothermund & Wentura, 2001Schwarz, 2007;Smith, 1996). Although researchers have repeatedly shown that the meaning of the same concept can vary across different contexts, it has proven difficult to predict when people assign which meaning to a concept.…”
mentioning
confidence: 99%
“…The notion that exposure to expectancy-violating information enhances attention has been adopted by Gawronski, Ye, Rydell, and De Houwer (2014) to investigate the integration of incidental context cues into the mental representation of newly acquired information. The basic idea underlying this work is that exposure to expectancy-violating information enhances attention to the momentary context, which leads to an integration of the context into the mental representation of the expectancy-violating information.…”
Section: Contextualized Representation Of Expectancy-violating Informmentioning
confidence: 99%